Locating Motivation for English as a Foreign Language Over Time: The Influence of School Location and Type - Canrinus, Esther T.; Scheffler, Paweł; Baranowska, Karolina (SAGE open, 2024)
This article examines secondary school learners’ motivation to learn English as a foreign language (EFL) in relation to two contextual factors: school type and school location. Data were collected from 352 Polish learners who attended English instruction in general and technical secondary schools in a large city and a small town in western Poland. Learners’ motivation, conceptualized as a continuum from fully autonomous to fully controlled, was measured through a survey at two time points, 2 years apart, which provided an assessment of motivational change. The second measurement was followed by interviews with selected learners. Our results show that learners from general secondary schools in the two locations exhibited different motivational patterns, while those from technical schools were similarly motivated regardless of their schools’ locations. A decrease in extrinsic motivation over time was observed in both types of small-town schools. Based on these results, we discuss the implications for EFL pedagogy. Plain Language Summary We investigate how the location and type of school may influence students’ motivation for learning English as a foreign language. We compared general and technical schools located in either a town or city in Poland. In total 352 Polish students completed a survey. Students from technical schools were similarly motivated regardless of their schools’ location. Students from general schools showed different motivational patterns depending on whether they were located in the town or in the city. Additionally, we investigated changes in students’ motivation and asked students how they would explain changes in their motivation. Over the period of 2 years, regardless of the type of school, the students from the town started perceiving their English classes less as an obligation and less as something to do as there is no other choice. Motivating students can at times require considerable effort from the teacher. Based on our findings, we advise teachers to take into account the type and location of school when designing their motivational teaching.